Salmonella spp. in non-edible animal products intended for the preparation of feed (meal) for industrial poultry feed (Research, Society and Development, 2022)
Non-edible by-products of animal origin are slaughter waste from slaughter animals that after processing give rise to animal meal which in turn is used as ingredients in the preparation of animal feed such as farm animals. Although this practice has its advantages in reducing environmental impact and meeting the nutritional needs of animals, it can serve as a vehicle for microorganisms such as Salmonella spp. Since food can play an important role in the dissemination of pathogens in the poultry production chain through feeding, the objective of the present study was to investigate the presence of Salmonella spp. samples of non-edible flours of animal origin used in the formulation of feed and also of feed produced from these by-products in slaughterhouses received from Bahia and Pernambuco states, Brazil and that are used in the industrial poultry farms of these States. Out of 649 samples of animal origin flours and feed were analyzed, of which 110 (16.9%) presented Salmonella spp. Statistical analysis, through descriptive analysis and Pearson’s chi-squase association test (X2) showed an association between the presence of Salmonella spp. and the different  types of inedible foods analyzed (p